THE ROLE OF COLLABORATIVE LEARNING IN SOCIETY (Modern education and development, 2025)
The article analyzes the importance and role of collaborative learning in society. It also highlights the role of collaborative learning in creating innovations and economic growth among specialists and groups from different strata of society. The article emphasizes the positive impact of collaborative learning in the development of society and its relevance.